EnglishThe Degree of Application of the Standards of the American National Council for Accreditation of Teacher Education (NCATE) in the Education College at the Hama University (Journal of Hama University, 2024)
The research aimed to determine the application of the American National Council for Accreditation of Difference in Preparation (NCATE) standards in the Education College in Hama University from the point of view of the educational staff members, and to know the differences in viewpoints according to the variables of (gender, administrative capacity, years of teaching experience, age, and the source of obtaining the last qualification). The sample consisted of (16) members of the teaching staff in the College of Education at the University of Hama, and used a questionnaire consisting of (48) items distributed on six dimensions and the research results showed the following: The degree of application of the standards of the American National Council for Accreditation of Teacher Education (NCATE) in the Education College at the Hama University from the point of view of the educational staff members was average. The criterion (diversity) ranked first with a high degree of approval, and the criterion (resources and wisdom) came in the last rank with a medium approval degree. There is no statistically significant difference between the mean scores of the sample members on the questionnaire according to the variables (gender, administrative capacity, number of years of teaching experience, age, source of obtaining the last educational qualification).